A teoria social do reconhecimento como fenômeno pedagógico: a relação teoria e prática - Arend, Carline Schröder (2012)
This research aims to reflect about the theoretical and practical knowledge involved during the formation of the pedagogue in Federal University of Santa Maria (Universidade Federal de Santa Maria UFSM), trying to comprehend, in the light of the theory of other recognition, what is hidden in the identity of the course. Using the analogy with the Jar Myth of Pandora (Mito da Jarra de Pandora), we realize that is important the constant movement of opening to the other, to what is different, even though there is the necessity to reveal that, in many moments, and this causes discomfort and conflicts. According to the theoretical contributions of critical theory, more specifically, from theory of other recognition, from Axel Honneth, the work tries to enable the comprehension of the role of the other in the formation, showing that, in this movement, when the self finds the other, he returns to himself different and enriched with new experiences. The same process occurs when theory and practice recognize themselves mutually, because both influence each other and constitute themselves from the discovery of the self in the other. The question that guided the research is leaded by the reflections and analysis anchored in the Philosophy of Education field, in this way: What are the new forms of sociability and acquaintance, the new living sources of recognition of the other, expressed in the social life, which could subsidize new comprehension of the relation between theory and practice in the pedagogical environment? In the same way of the theory of recognition, the educational dilemma theory and practice notices the necessity to amplify the discussion beyond the school environment, considering also the education as a social phenomenon that permeates the instances of family, state and society as a whole. These instances are present in the genesis of the educational constitution and, thus, there are possibilities that appear to think and reflect about the pedagogical production anchored in the other recognition.